2012
DOI: 10.1063/1.3692757
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic superlens-enhanced inductive coupling for wireless power transfer

Abstract: We investigate numerically the use of a negative-permeability "perfect lens" for enhancing wireless power transfer between two current carrying coils. The negative permeability slab serves to focus the flux generated in the source coil to the receiver coil, thereby increasing the mutual inductive coupling between the coils. The numerical model is compared with an analytical theory that treats the coils as point dipoles separated by an infinite planar layer of magnetic material [Urzhumov et al., Phys. Rev. B 19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
76
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 42 publications
1
76
1
Order By: Relevance
“…Techniques such as tuning the frequency of operation, employing impedancematching networks [16], [17], [18], transponder configurations [19], [20], coil arrays [21], and the use of a superlens to enhance coupling [22] have been explored. In [23], [24], [25], constant efficiencies were maintained by tuning a WNPT system's operating frequency while the transmit and receive resonators were strongly coupled.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as tuning the frequency of operation, employing impedancematching networks [16], [17], [18], transponder configurations [19], [20], coil arrays [21], and the use of a superlens to enhance coupling [22] have been explored. In [23], [24], [25], constant efficiencies were maintained by tuning a WNPT system's operating frequency while the transmit and receive resonators were strongly coupled.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] In recent years, it has been shown that efficient mid-range wireless transfer can be achieved by utilizing near field magnetic coupling between two identical resonators. 2-5, 7, 9-13 Resonance frequency matching, resonance with high quality factors, and fast coupling rate are the keys to achieve high efficiency wireless power transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Radiant WPT technology relies on the transfer of the electromagnetic waves, which could be widely applied in space transfer and satellite solar power station. Inductive coupling WPT is also an efficient technique brought into practice, but it can only be used as a short-distance WPT [3].…”
Section: Introductionmentioning
confidence: 99%